How to deal with the past? How collective and historical trauma psychologically reverberates in Eastern Europe - Maercker, Andreas (Frontiers in Psychiatry, 2023)
Traumatic stress studies have recently addressed the issue of ‘historical trauma’ that well explain the impact of collective or totalitarian trauma. The example of former communist Eastern Europe shows that there are many individual and socio-psychological consequences that still have effects today. This paper summarizes concepts and findings on ‘historical traumas’ that describe such long-lasting effects. The focus is on the side of the victims and their family descendants and thus also on the moral heirs of the dissidents, e.g., the Russian NGO Memorial. Analogous to developments in psychotraumatology, increasing knowledge in this area can explain psychosocial pathologies but also help develop effective remedies. This includes the development of a culture of remembrance, socio-therapeutic interventions and increased sensitivity towards those patients and clients who have such a personal legacy.